P Pengaruh Hukum Agama Terhadap Praktik Perkawinan Adat di Kulawi Selatan - Faren Chrismac (TERAJU: Jurnal Syariah dan Hukum, 2026)
The purpose of this study is to analyse the implementation of traditional marriage in South Kulawi and to examine the influence of religious law on traditional marriage law in South Kulawi. In this study, the author employs an empirical juridical research method, utilising data collection techniques such as observation, interviews, and document analysis. The findings of this study indicate that the implementation of traditional marriage in South Kulawi continues to uphold customary law as an ancestral heritage possessing sacred value and serving as a cultural identity for the community. Each stage of the process, starting from mampewiwi (asking), mekamaro (proposal), memua (marriage ceremony), and mepantodui (acceptance of the daughter-in-law), is carried out using the customary language, reflecting efforts to preserve traditions amidst the tide of modernisation. On the other hand, religion has a significant influence on the implementation of traditional marriage. Through the process of inculturation, religious values are integrated into every stage of the tradition, playing a role in providing moral and spiritual guidance for the observance of customs, particularly in determining the validity of a marriage according to the Christian faith. Although customs remain the foundation for the conduct of marriage, religion imposes certain restrictions, such as not blessing marriages resulting from adultery and not permitting marriages involving individuals under the age of nineteen. Thus, customs and religion complement one another in maintaining the sanctity, morality, and preservation of the cultural values of the South Kulawi community.